THE IMPACT OF CREDIT ASSET QUALITY ON MARKET VALUE AND TRADING VOLUME: AN ANALYTICAL STUDY OF A SAMPLE OF IRAQI BANKS FOR THE PERIOD 2014-2023 - Maec alreem Khudhair Abbas; Assistant Lecturer Manaf Mohammed Khaleel (Scholars Digest Publishing, 2025)
Since the Great Financial Crisis, non-performing loans have received significant attention and have been the focus of discussions in the financial sector. In this study, we attempt to demonstrate the size of the non-performing loan ratio for a sample of operating commercial banks. We also attempt to demonstrate the relationship between these ratios and market indicators (trading volume and market value) using simple linear regression and the Pearson correlation coefficient. The study concluded that the impact of credit asset quality (non-performing loan ratio) on market value is not constant, as a statistically significant relationship was found in some banks in the study sample, but not in others. This may indicate that credit asset quality may be affected by other factors, such as the economic situation or the nature of the banking market. The results also showed that credit asset quality has a more stable relationship with trading volume than with market value, as there was a statistically significant direct relationship between three out of four banks, indicating that investors respond to the level of credit risk when making trading decisions. The study also recommended enhancing credit risk management in commercial banks in general, and the banks in the study sample in particular, by establishing effective mechanisms to monitor and reduce non-performing loans, which would be reflected in the Increased investor confidence in the financial market.
Keywords: Credit asset quality, non-performing loan ratio, trading volume market capitalization.